Utilization of ICT Resources for Teaching among Some Selected Lecturers in Colleges of Education in Kwara State - Daramola, Florence Olutunu (ASEAN Journal of Educational Research and Technology, 2023)
The successful integration of Information and Communication Technology (ICT) resources into teaching and learning depends on the ability of lecturers to structure their learning environment to merge technology traditionally. This study examined the utilization of ICTs resources for teaching among selected lecturers in Kwara state. The study adopted descriptive research of the survey type. The population of this study was made up of all college of education students in Kwara State. Proportional sampling techniques were used to allocate several respondents in each school based on their estimated population using Israel Model. The instrument for data collection was an adapted questionnaire. Descriptive and Inferential statistics were used to answer the research question and test the stated hypotheses with the aid of statistical product and service solution (SPSS) version 20.0 at a 0.05 level of significance. The findings indicated that lecturers utilize ICT resources for teaching. No significant difference exists in the lecturer’s level of utilization of ICT resources for teaching based on the area of specialization.